GAMBARAN PERILAKU IBU RUMAH TANGGA TENTANG PENANGGULANGAN DIARE PADA BALITA DI DESA MANGON KECAMATAN SANANA KABUPATEN KEPULAUAN SULA PROVINSI MALUKU UTARA - Mus, Agriati Yulin; Kandou, Grace D.; Maramis, Franckie R. R. (e-Biomedik, 2013)
Abstract: Diarrhea is a disease characterized by changes in the shape and consistency of stools which becomes soft until watery and increase of the frequency of defecation (more than normal three times a day). North Maluku province is one of the islands in Indonesia which is prone to diarrhea. Data of North Maluku Provincial Health Office showed that most children with diarrhea in Mangon village were under five years. This study aimed to find a description of the housewives’ behaviour in diarrhea management in children under five years in Mangon village, Sanana Sula Islands, North Maluku Province. This study was a descriptive survey. There were 91 respondents in accordance with the number of cases of diarrhea in children under five. The results showed that the knowledge about diarrhea management were categorized as good in 75 respondents (82.4%); the mother's attitude were categorized as good in 48 respondents (52.7%); and the mothers’ actions in diarrhea management were categorized as good enough in 63 respondents (69.2%). Conclusion: Most mothers of children under five in Mangon village Sanana Sula Islands, North Maluku Province were categorized as good related to their knowledge and attitude in diarrhea management, and were categorized as good enough related to their actions. Keywords: behavior, housewives, handling of diarrhea, children under five Abstrak: Diare adalah penyakit yang ditandai dengan perubahan bentuk dan konsistensi tinja lembek atau cair dan bertambahnya frekuensi buang air besar lebih dari biasanya (tiga kali dalam sehari). Provinsi Maluku Utara merupakan salah satu wilayah kepulauan di Indonesia yang rawan dengan gejala diare. Data yang diperoleh dari Dinas Kesehatan Propinsi Maluku Utara menunjukkan bahwa kasus diare terbanyak terdapat di Desa Mangon Kecamatan Sanana Kabupaten Sula yang terutama dijumpai pada balita. Tujuan penelitian untuk mengetahui gambaran perilaku ibu rumah tangga tentang penanggulangan diare pada balita di Desa Mangon Kecamatan Sanana Kabupaten Kepulauan Sula Provinsi Maluku Utara. Metode penelitian ini bersifat deskriptif dengan menggunakan metode survei. Jumlah sampel sebanyak 91 responden sesuai dengan jumlah kasus diare pada balita. Hasil penelitian memperihatkan bahwa pengetahuan ibu tentang penanggulangan diare pada anak balita di desa Mangon termasuk kategori baik sebanyak 75 responden (82,4 %), sikap ibu balita yang termasuk kategori baik sebanyak 48 responden (52,7%), dan tindakan ibu balita termasuk kategori cukup sebanyak 63 responden (69,2 %). Simpulan: Sebagian besar pengetahuan dan sikap ibu balita terhadap penanggulangan diare di desa Mangon Kecamatan Sanana Kabupaten Sula Propinsi Maluku Utara termasuk kategori baik sedangkan tindakan penanggulangan diare termasuk kategori cukup. Kata Kunci: perilaku, ibu rumah tangga, penaggulangan diare, balita.